A high reliability module with thermoelectric device by molding technology for M2M wireless sensor network. (24th September 2015) - Nakagawa, K; Tanaka, T; Suzuki, T
Abstract: This paper presents the fabrication of a new energy harvesting module that uses a thermoelectric device (TED) by using molding technology. Through molding technology, the TED and circuit board can be properly protected and a heat-radiating fin structure can be simultaneously constructed. The output voltage per heater temperature of the TED module at 20 °C ambient temperature is 8 mV K −1, similar to the result with the aluminum heat sink which is almost the same fin size as the TED module. The accelerated environmental tests are performed on a damp heat test, which is an aging test under high temperature and high humidity, highly accelerated temperature, and humidity stress test (HAST) for the purpose of evaluating the electrical reliability in harsh environments, cold test and thermal cycle test to evaluate degrading characteristics by cycling through two temperatures. All test results indicate that the TED and circuit board can be properly protected from harsh temperature and humidity by using molding technology because the output voltage of after-tested modules is reduced by less than 5%. This study presents a novel fabrication method for a high reliability TED-installed module appropriate for Machine to Machine wireless sensor networks.